Understanding public perceptions of risk regarding outdoor pet cats to inform conservation action. Issue 2 (8th January 2016) - Gramza, Ashley; Teel, Tara; VandeWoude, Susan; Crooks, Kevin
Abstract: Free‐ranging domestic cats (Felis catus) incur and impose risks on ecosystems and represent a complex issue of critical importance to biodiversity conservation and cat and human health globally. Prior social science research on this topic is limited and has emphasized feral cats even though owned cats often comprise a large proportion of the outdoor cat population, particularly in urban areas. To address this gap, we examined public risk perceptions and attitudes toward outdoor pet cats across varying levels of urbanization, including along the wildland–urban interface, in Colorado (U.S.A.), through a mail survey of 1397 residents. Residents did not view all types of risks uniformly. They viewed risks of cat predation on wildlife and carnivore predation on cats as more likely than disease‐related risks. Additionally, risk perceptions were related to attitudes, prior experiences with cats and cat–wildlife interactions, and cat‐owner behavior. Our findings suggest that changes in risk perceptions may result in behavior change. Therefore, knowledge of cat‐related risk perceptions and attitudes could be used to develop communication programs aimed at promoting risk‐aversive behaviors among cat owners and cat‐management strategies that are acceptable to the public and that directly advance the conservation of native species.